2013
DOI: 10.1186/1477-7827-11-41
|View full text |Cite
|
Sign up to set email alerts
|

The new Rapid-i carrier is an effective system for human embryo vitrification at both the blastocyst and cleavage stage

Abstract: BackgroundThe Rapid-i is a new FDA cleared closed carrier for embryo vitrification. The cooling rate of - 1220°C/min is far lower than that reported with open vitrification systems such as the cryoloop (−15,000°C/min). Little published data is currently available on this device. This study presents our initial clinical data, as well as live birth outcomes, with the Rapid-i. The efficacy of this device for the cryopreservation of cleavage, as well as blastocyst stage human embryos is also analyzed. We further c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…These findings confirm earlier results, which showed that warmed blastocysts that survived vitrification were not different from fresh blastocysts, in terms of quality, DNA and chromosome integrity, ultrastructure, and developmental competence [11,17,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings confirm earlier results, which showed that warmed blastocysts that survived vitrification were not different from fresh blastocysts, in terms of quality, DNA and chromosome integrity, ultrastructure, and developmental competence [11,17,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 92%
“…Others formulations are DMSO-free: some still employ small devices and require very small vitrification volumes (eg. Rapid-I™ kit, Vitro Life, Sweden, [11]), while others are volume independent, use larger straws which are easier to handle and allow for longer embryo exposure to vitrification solutions (e.g. Global Fast Freeze kit, LifeGlobal, LLC, Canada, [12,13]).…”
Section: Introductionmentioning
confidence: 99%
“…For warming, only embryos and cooling device, which were not exposed to liquid nitrogen, were warmed in thawing solution, thus avoiding the risk of contamination. Recently, it has been reported that the implantation potential of human blastocyts vitrified with Rpid-i was comparable to that of counterparts with an open device [6]. However, the data was mixed with single and multiple blastocyst transfer, and the number of patients (22) was small.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these embryos are vitrified, cryopreserved, and warmed without direct exposure to liquid nitrogen. Another research group also revealed no significant difference between the use of closed and open vitrification systems in the survival rate or implantation rate [25]. Recently, a total of 114 infants were obtained from blastocysts vitrified using the same closed vitrification device [25] and another closed device [26].…”
Section: Introductionmentioning
confidence: 99%
“…Such cross-contamination could arise from direct contact of the solution containing the oocytes and embryos with the liquid nitrogen. Therefore, to avoid the possible risk of contamination, closed vitrification systems have been developed [15][16][17][18][19][20][21][22][23][24][25]. However, new concerns such as a potential rise in temperature caused by a heat sealer and a decrease in the cooling rate have emerged with these methods.…”
Section: Introductionmentioning
confidence: 99%